Harvesting Microalgae for Food and Energy Products. Issue 10 (16th July 2020) - Liber, Julian A.; Bryson, Abigail E.; Bonito, Gregory; Du, Zhi‐Yan
Abstract: Microalgae are promising biological factories for diverse natural products. Microalgae tout high productivity, and their biomass has value in industrial products ranging from biofuels, feedstocks, food additives, cosmetics, pharmaceuticals, and as alternatives to synthetic or animal‐derived products. However, harvesting microalgae to extract bioproducts is challenging given their small size and suspension in liquid growth media. In response, technologic developments have relied upon mechanical, chemical, thermal, and biological means to dewater microalgal suspensions and further extract bioproducts. In this review, the effectiveness and considerations were evaluated for the implementation of microalgae harvesting techniques. Nonbiological methods—filtration, chemical, electrical, and magnetic nanoparticle flocculation, centrifugation, hydrothermal liquefaction, and solvent‐based extraction, as well as biological coculture‐based methods are included. Recent advances in coculture algae‐flocculation technologies that involve bacteria and fungi are summarized. These produce a variety of natural bioproducts, which show promise in fuel and food additive applications. Furthermore, this review addresses the developments of genetic tools and resources to optimize the productivity and harvesting of microalgae or to provide new bioproducts via heterologous expression. Finally, a glimpse of future biotechnologies that will converge to produce, harvest, and process microalgae using sustainable and cost‐effective methods is offered. Abstract : Here the effectiveness and considerations are evaluated for the implementation of microalgae harvesting techniques and conventional and newer biological coculture‐based methods are included. This review also addresses the developments of genetic tools and resources to optimize the productivity and harvesting of microalgae, as well as a glimpse of future biotechnologies that will converge to produce, harvest, and process microalgae.